O professor de matemática e o trabalho com medidas separatrizes - Canossa, Roberto (2009)
The study of Statistics became, in 1997, part of the curriculum of basic school, therefore, the preparation of the mathematics teachers became necessary in order to approach this theme, once many of the teachers either did not have this content in his/her initial formation or had it, but in a superficial way. The surveys performed by our group have also shown these results. These results and the great difficulties some mathematics teachers from public schools, especially in Diadema, have in developing, with the students, the Statistics contents and its interpretations is our motivation to the realization of this paper. In order to do so, we intended to answer the following question of research: What are the didactics characteristics to a continued formation to High School teachers, aiming at working with concepts of median and quartiles, so that students will be able to make decisions from the analysis of the realized variation, with the help of Dot-Plot and Box-Plot? To such verification, we have elaborated and applied a diagnose questionnaire (appendix 1), we have realized continued formation workshops from the results of these questionnaires, and, at last, we have observed a class from a volunteer teacher. We could notice that the majority of teachers do not work the concepts of median and quartiles: they limit themselves to the concept of mean, variance and standard deviation, inserted only as mathematics formulas, without giving sense to such concepts; besides, they do not have knowledge of the graphs Dot-Plot and Box-Plot. The workshop allowed an advancement concerning reasoning and statistical literacy to the volunteer teacher. However, we could realize that the two sections of workshop were not enough to get to level 5 (integrated process reasoning) of statistical reasoning proposed by Garfield (2002)